Pengaruh Pemanfaatan Artificial Intelligence (AI) dalam Pembelajaran Bahasa Indonesia Terhadap Minat Belajar Peserta Didik Kelas IV Sekolah Dasar - Aftin Nazakia; Heru Purnomo; Deri Anggraini (Universitas Muhammadiyah Bangka Belitung, 2025)
The rapid development of technology in the digital era requires the world of education to adapt, including in how to deliver learning materials. One of theinnovations that are starting to be widely applied is the use of Artificial Intelligence (AI) as a learning medium. Finding out how employing AI-based media affects students' enthusiasm in learning Indonesian is the aim of the study. This study employed a quantitative approach using a One Group Pretest-Posttest methodology. Students in the fourth grade of SD Negeri Mejing 2 are the research subjects. A questionnaire that was given both before and after the therapy served as the study tool. The investigation proceeded with the Paired Sample T-Test after the normality test findings indicated that data was distributed normally. The findings of the analysis indicate a substantial change in learning interest before and after the therapy, with a significance value of 0.000 (p < 0.05). This finding proves that AI-based media plays a role in increasing children' excitement for studying. Thus, the integration AI technology can be an effective alternative to create a more engaging and meaningful learning experience at the elementary school level.